Pengaruh Model Cooperative Script Terhadap Pemahaman Siswa Materi Pecahan Biasa Kelas IV SD Negeri 10 Sungailiat - Mona, Monalisa; Fitri Apriani; Sisi Pitriyana (Universitas Muhammadiyah Bangka Belitung, 2024)
The students’ struggle to understand and use common fractions correctly, especially when dealing with fractions with different denominators, was the driving force behind this study. Researchers at SD Negeri 10 Sungailiat set out to test fourth graders’ understanding of common fractions using the Cooperative Script model. A quantitative study using a pre-experimental design based on a one-group pretest-posttest was used. In this study, saturated sampling was used for the sample. 27 fourth graders from SD Negeri 10 Sungailiat participated in the study. Ten questions covering common fractions served as the test data collection tool. A paired sample t-test was used to test the hypothesis and ensure the normality of the data. There was a statistically significant relationship between the use of common fractions material in the pretest and posttest. The value found 0.00<0.05 in the calculation of the paired sample t-test using SPSS 26 shows this. This proves that Ha is true and H0 is false. Fourth graders of SD Negeri 10 Sungailiat benefited from the approach through the Cooperative Script model in learning fractions.